2014
DOI: 10.1103/physreve.89.052811
|View full text |Cite
|
Sign up to set email alerts
|

Generalized epidemic process on modular networks

Abstract: Social reinforcement and modular structure are two salient features observed in the spreading of behavior through social contacts. In order to investigate the interplay between these two features, we study the generalized epidemic process on modular networks with equal-sized finite communities and adjustable modularity. Using the analytical approach originally applied to clique-based random networks, we show that the system exhibits a bond-percolation type continuous phase transition for weak social reinforcem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…Finally, we can readily apply the methods discussed here to more general kinds of random networks with Table I are used. locally tree-like structures, such as scale-free networks whose structural heterogeneity would certainly affect the phase diagram and critical behaviors in nontrivial ways [26]. Addressing these issues would broaden our knowledge about universal features of contagion under the influence of cooperative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we can readily apply the methods discussed here to more general kinds of random networks with Table I are used. locally tree-like structures, such as scale-free networks whose structural heterogeneity would certainly affect the phase diagram and critical behaviors in nontrivial ways [26]. Addressing these issues would broaden our knowledge about universal features of contagion under the influence of cooperative effects.…”
Section: Discussionmentioning
confidence: 99%
“…The model features an infection probability which changes according to the number of contacts with infected individuals. It has been shown that both continuous and discontinuous transitions are possible on regular lattices [3,7] and random networks [3,8,9], with scaling properties belonging to the bond percolation universality class [3,7,9] in the vicinity of critical points. Intermediate tricritical behaviors were also studied by a field-theoretical approach, whose notable differences from the ordinary bond percolation behaviors include the change of the upper critical dimension from 6 to 5 and the breakdown of symmetry * msha@chosun.ac.kr † hjeong@kaist.edu between the percolation probability and the giant cluster size [7].…”
Section: Introductionmentioning
confidence: 99%
“…Next we recall discontinuous percolation transitions occurring in generalized contagion models [12][13][14]. Recent studies [15] of a generalized epidemic model [13] revealed that the discontinuous percolation transition turns out to be a hybrid percolation transition (HPT) represented by (1). For this case, a HPT is induced by cluster merging processes.…”
mentioning
confidence: 99%
“…5(b). Finally, for studying the effect of correlations between IETs on the spreading in a simpler setup, we introduce two-step deterministic SI ("2DSI" in short) dynamics [54] as a variation of generalized epidemic processes [57][58][59][60], see Fig. 5(c).…”
Section: Effects Of Correlations Between Iets On Dynamical Procementioning
confidence: 99%